Screens as Battlefields: Fact-Checkers’ Multidimensional Challenges in Debunking Russian-Ukrainian War Propaganda - Laurence Dierickx; Carl-Gustav Lindén (Media and Communication)
This study examines the challenges fact-checkers face when dealing with war propaganda and how their socio-professional contexts influence these obstacles. Using a mixed-methods approach, the research identifies common difficulties such as time constraints, resource limitations, and the struggle to find reliable information amidst language barriers and geographical distances. The findings highlight the impact of socio-professional contexts on investigative methods, ranging from traditional journalism to advanced open-source intelligence methods. The study underscores the importance of international cooperation and support networks in addressing these challenges and also in mitigating the impact that exposure to violent content and harassment has on well-being and professional integrity.